2021
DOI: 10.3389/pore.2021.631969
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Survivin Protein Levels in Lung Cancer Patients Treated With Platinum-Based Chemotherapy

Abstract: The survivin protein contributes to the development and progression of tumors. Protein expression and mRNA levels correlate with clinicopathological parameters and survival of cancer patients. Our purpose was to evaluate whether circulating survivin levels have any diagnostic or predictive value in lung cancer. 118 patients with advanced stage lung cancer participated in our study. 53 suffered from adenocarcinoma (ADC), 33 from squamous cell carcinoma (SqCC), and 32 from small cell lung cancer (SCLC). We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Although rarely observed in well-differentiated tissues, it has been seen as highly expressed in tumor tissues which indicate its promotional role in tumorigenesis ( 3 , 4 ). Previous studies have revealed that survivin may act as an oncogene in lung cancer ( 5 ), colon cancer ( 6 ), pancreatic cancer ( 7 ), prostate cancer ( 8 ), breast cancer ( 9 ), lymphoma ( 10 ), and EC ( 3 ). Vallböhmer et al demonstrated that survivin was significantly upregulated in esophageal adenocarcinoma compared to the adjacent normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Although rarely observed in well-differentiated tissues, it has been seen as highly expressed in tumor tissues which indicate its promotional role in tumorigenesis ( 3 , 4 ). Previous studies have revealed that survivin may act as an oncogene in lung cancer ( 5 ), colon cancer ( 6 ), pancreatic cancer ( 7 ), prostate cancer ( 8 ), breast cancer ( 9 ), lymphoma ( 10 ), and EC ( 3 ). Vallböhmer et al demonstrated that survivin was significantly upregulated in esophageal adenocarcinoma compared to the adjacent normal tissues.…”
Section: Introductionmentioning
confidence: 99%